WATER AND VEGETATION COVER CHANGE DETECTION USING MULTISPECTRAL SATELLITE IMAGERY: A CASE STUDY ON JHENAIDAH DISTRICT OF BANGLADESH - Bashar, Abul; Haque, Md. Inzamul; Parvin, Most. Atia; Hossain, Md. Anik (Bangladesh Journal of Multidisciplinary Scientific Research, 2023)
Water and vegetation are the two most important land cover features of any natural setting. The Jhenaidah District of Bangladesh is known for its remarkable physical geography, featuring diversified vegetation cover and numerous oxbow lakes. Due to several anthropogenic causes, this majestic land cover is degrading rapidly. This study examines the study area’s spatiotemporal water and vegetation cover change from 1990 to 2020. Freeware Satellite imageries from the USGS data archive were used as the main secondary data source, ensuring consistency by collecting dry season images. In addition, open discussions with the residents provided valuable insights into the situation. Remote sensing (RS) based Soil Adjusted Vegetation Index (SAVI) was used to detect the water and vegetation cover from the preprocessed satellite imageries. Furthermore, the water and vegetation cover were classified based on a scheme developed by field observation and discussion with the residents. The analysis reveals an overall 84.47% decline in dense vegetation, 63.01% decline in deep water cover, 185.69% increase in shallow water cover, and 16.08% increase in agricultural lands within the mentioned time frame. Almost all the upazila of Jhenauidah district experience the criticality of the land cover change. Among the upazila, Shailkupa faced an unprecedented decline in deep water (95.29%), and Kaliganj faced a heavy decrease in forested vegetation (92.40%). In contrast, shallow water expanded significantly in Sadar Upazila (251.37%), and agricultural land experienced the most increasing trend (32.70%) in Shailakupa Upazila. JEL Classification Codes: C21, Q24, Q25.